Parabronchial remodeling in chicks in response to embryonic hypoxia - do Amaral-Silva, Lara [UNESP]; Lambertz, Markus; Zara, Fernando José [UNESP]; Klein, Wilfried [UNESP]; Gargaglioni, Luciane Helena [UNESP]; Bıćego, Kênia Cardoso [UNESP] (The Company of Biologists, 2019)
The embryonic development of parabronchi occurs mainly during the second half of incubation in precocious birds, which makes this phase sensitive to possible morphological modifications induced by O2 supply limitation. Thus, we hypothesized that hypoxia during the embryonic phase of parabronchial development induces morphological changes that remain after hatching. To test this hypothesis, chicken embryos were incubated entirely (21 days) under normoxia or partially under hypoxia (15% O2 during days 12 to 18). Lung structures, including air capillaries, blood capillaries, infundibula, atria, parabronchial lumen, bronchi, blood vessels larger than capillaries and interparabronchial tissue, in 1- and 10-day-old chicks were analyzed using light microscopy-assisted stereology. Tissue barrier and surface area of air capillaries were measured using electron microscopy-assisted stereology, allowing for calculation of the anatomical diffusion factor. Hypoxia increased the relative volumes of air and blood capillaries, structures directly involved in gas exchange, but decreased the relative volumes of atria in both groups of chicks, and the parabronchial lumen in older chicks. Accordingly, the surface area of the air capillaries and the anatomical diffusion factor were increased under hypoxic incubation. Treatment did not alter total lung volume, relative volumes of infundibula, bronchi, blood vessels larger than capillaries, interparabronchial tissue or the tissue barrier of any group. We conclude that hypoxia during the embryonic phase of parabronchial development leads to a morphological remodeling, characterized by increased volume density and respiratory surface area of structures involved in gas exchange at the expense of structures responsible for air conduction in chicks up to 10 days old.
Keywords: Air capillary; Blood capillary; Blood–gas tissue barrier; Chicken; Incubation; Lung